Lack of implementing Building Information Modelling in the quantity surveying profession. Issue 1 (February 2021) - Gilchrist, C R; Cumberlege, R; Allen, C
Abstract: Quantity surveyors possess an inherent traditionalism when it comes to Building Information Modelling (BIM), preferring to follow current trends and methods rather than taking a proactive approach towards its implementation. This implicates that there is still a lack of understanding of the potential uses and benefits that BIM software will provide the profession. Within this context, the purpose of the research was to determine the reasons why professional quantity surveyors (PrQS) are not utilising BIM to improve their day-to-day tasks and functions. To conduct the research, a qualitative study was carried out using semi-structured interviews with PrQSs from various QS firms situated in Port Elizabeth. This method of data collection allowed for a more in-depth understanding of why these professionals are not utilising BIM in Port Elizabeth. The research investigated the reasons behind these PrQSs not utilising BIM to improve current methods of managing construction costs on projects. The results revealed that there are challenges that QSs face in the construction industry in terms of their working methods. The results also identified the potential of BIM to help mitigate these challenges with interviewees mentioning several benefits that the BIM software will provide for the QS. Despite BIM's potential in the QS profession, the results showed that there are still several barriers holding professionals back, the most prominent being the lack of senior leadership support, knowledge of BIM, a lack of full team integration and the cost of implementing BIM. The main limitation of the study was that the number of responses was limited due to the fact that very few quantity surveyors were experienced in, or, had knowledge about BIM. As degrees of regional sentiment, and industry development also had influence on participants' answers, the findings may not be suitable or be generalised to other provinces in South Africa. The findings will assist all stakeholders in the QS profession, as they will be more informed about potential benefits and challenges to BIM implementation, which will provide them with greater knowledge of how it works and precisely what it is capable of doing.